2019
DOI: 10.1002/ijgo.12957
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus knowledge, contraception use, and lessons learned from a Dominican Republic pilot study

Abstract: Objective To assess knowledge of the Zika virus (ZIKV), use of contraceptives, and sources of health information in rural communities in the Dominican Republic. Methods Over 4 days in March 2017, a research team traveled to four rural communities in the Dominican Republic to provide healthcare services. Overall, 90 men and women consented to a voluntary verbal 12‐question survey. Results Of the participants, 55% were not certain whether ZIKV is transmitted sexually; 75% of participants were either not sure or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Of the 46 included documents, 45 were published in English and one in Spanish. Of the peer-reviewed documents there was heterogeneity in study designs (based on MMAT classification), which included twenty qualitative studies [8, 21-24, 26, 29, 32, 35, 36, 38, 47-54, 56] , nine cross-sectional mixed method studies [27, 30, 31, 37, 57-61] , one cluster randomised controlled trial [62] , four descriptive studies [63-66] two reviews [67, 68] , three surveys [34, 69, 70] , one cohort study [33] , one pre-post design study [71] , and, four opinion and commentary essays [28, 72-74] . The majority of the studies was performed in Brazil (n=10) and in Puerto Rico (n=6), moreover in Mexico (n=5) Colombia (n= 4), Peru (n=4), Dominican Republic (n=3), Guatemala (n=2), Honduras (n=2), Ecuador (n=2), Cuba (n=2), Nicaragua (n=1), French Guyana (n=1), Uruguay (n=2), Belize (n=1), Curacao (n=1) and Argentina (n=1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 46 included documents, 45 were published in English and one in Spanish. Of the peer-reviewed documents there was heterogeneity in study designs (based on MMAT classification), which included twenty qualitative studies [8, 21-24, 26, 29, 32, 35, 36, 38, 47-54, 56] , nine cross-sectional mixed method studies [27, 30, 31, 37, 57-61] , one cluster randomised controlled trial [62] , four descriptive studies [63-66] two reviews [67, 68] , three surveys [34, 69, 70] , one cohort study [33] , one pre-post design study [71] , and, four opinion and commentary essays [28, 72-74] . The majority of the studies was performed in Brazil (n=10) and in Puerto Rico (n=6), moreover in Mexico (n=5) Colombia (n= 4), Peru (n=4), Dominican Republic (n=3), Guatemala (n=2), Honduras (n=2), Ecuador (n=2), Cuba (n=2), Nicaragua (n=1), French Guyana (n=1), Uruguay (n=2), Belize (n=1), Curacao (n=1) and Argentina (n=1).…”
Section: Resultsmentioning
confidence: 99%
“…[29-31, 61, 74] Many publications assessed the level of knowledge, healthcare barriers and sexual health care through interviews, focus groups and surveys. [8, 21-24, 26, 27, 36-38, 47, 52-54, 56, 60, 63, 70] The implemented public health projects can be summarized and categorized into four broad key topics: 1) Mosquito vector control initiatives, 2) Contraception and reproductive healthcare, 3) Family support programmes and 4) Assessment of knowledge, perception and barriers. Almost all studies reported intervention effectiveness and improvement or changes in behaviour.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations